(3t+2q)(7t-9q)=

Simple and best practice solution for (3t+2q)(7t-9q)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3t+2q)(7t-9q)= equation:


Simplifying
(3t + 2q)(7t + -9q) = 0

Reorder the terms:
(2q + 3t)(7t + -9q) = 0

Reorder the terms:
(2q + 3t)(-9q + 7t) = 0

Multiply (2q + 3t) * (-9q + 7t)
(2q * (-9q + 7t) + 3t * (-9q + 7t)) = 0
((-9q * 2q + 7t * 2q) + 3t * (-9q + 7t)) = 0

Reorder the terms:
((14qt + -18q2) + 3t * (-9q + 7t)) = 0
((14qt + -18q2) + 3t * (-9q + 7t)) = 0
(14qt + -18q2 + (-9q * 3t + 7t * 3t)) = 0
(14qt + -18q2 + (-27qt + 21t2)) = 0

Reorder the terms:
(14qt + -27qt + -18q2 + 21t2) = 0

Combine like terms: 14qt + -27qt = -13qt
(-13qt + -18q2 + 21t2) = 0

Solving
-13qt + -18q2 + 21t2 = 0

Solving for variable 'q'.

Factor a trinomial.
(-2q + -3t)(9q + -7t) = 0

Subproblem 1

Set the factor '(-2q + -3t)' equal to zero and attempt to solve: Simplifying -2q + -3t = 0 Solving -2q + -3t = 0 Move all terms containing q to the left, all other terms to the right. Add '3t' to each side of the equation. -2q + -3t + 3t = 0 + 3t Combine like terms: -3t + 3t = 0 -2q + 0 = 0 + 3t -2q = 0 + 3t Remove the zero: -2q = 3t Divide each side by '-2'. q = -1.5t Simplifying q = -1.5t

Subproblem 2

Set the factor '(9q + -7t)' equal to zero and attempt to solve: Simplifying 9q + -7t = 0 Solving 9q + -7t = 0 Move all terms containing q to the left, all other terms to the right. Add '7t' to each side of the equation. 9q + -7t + 7t = 0 + 7t Combine like terms: -7t + 7t = 0 9q + 0 = 0 + 7t 9q = 0 + 7t Remove the zero: 9q = 7t Divide each side by '9'. q = 0.7777777778t Simplifying q = 0.7777777778t

Solution

q = {-1.5t, 0.7777777778t}

See similar equations:

| u+25=-61 | | 5r^2-55r+15=0 | | cos(x)+cox(7x)-cox(4x)=0 | | 89=n+3 | | 15y^3+12y^2+6y= | | 2+0.3y=11 | | 2(7x+5)=3(3x-2) | | 9(m)=25(m)+22 | | 6m+14m=-16 | | 6b^2=-18b | | 21=2p-9 | | 40+3x+20-5x=30 | | G+2g+6=6g-21 | | 20x-27=73 | | 5(z)+8=4(z)+20 | | 1.3x+3=-1 | | -6x+9y=84 | | 2w-21.5=9 | | 2x-3y=-28 | | 40-4x=2-10 | | -24y^3-64y^2=0 | | (Y^2+3)(y^2-12)=0 | | 7(x-2)=4(x+5) | | 7x-28=6x-1 | | 3(X+4)+7X=4 | | 8+3b=2(9-b) | | 2f+700=-74 | | -10p+9p=13 | | (x-10)(x+2)= | | k(k-1)-30=0 | | 20+18k=956 | | (7y-10y)-11+3=7 |

Equations solver categories